2015
DOI: 10.1002/brb3.369
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of somatosensory finger areas using vibrotactile stimulation, an ECoG study

Abstract: BackgroundIn surgical planning for epileptic focus resection, functional mapping of eloquent cortex is attained through direct electrical stimulation of the brain. This procedure is uncomfortable, can trigger seizures or nausea, and relies on subjective evaluation. We hypothesize that a method combining vibrotactile stimulation and statistical clustering may provide improved somatosensory mapping.MethodsSeven pediatric candidates for surgical resection underwent a task in which their fingers were independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
(79 reference statements)
3
11
0
Order By: Relevance
“…Specifically, the location of clusters in the pre‐ and post‐central gyri were relatively consistent with our fMRI maps, our TMS maps (Fig. ), and with areas responsible for sensorimotor representation of the fingers elucidated through electrocorticographic and brain stimulation techniques [Penfield and Boldrey, ; Wahnoun et al, ]. The neighboring clusters seen in the right SMA were also within the TMS and fMRI maps from our study, and consistent with previous findings that this area plays a role in motor training [Taubert et al, ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, the location of clusters in the pre‐ and post‐central gyri were relatively consistent with our fMRI maps, our TMS maps (Fig. ), and with areas responsible for sensorimotor representation of the fingers elucidated through electrocorticographic and brain stimulation techniques [Penfield and Boldrey, ; Wahnoun et al, ]. The neighboring clusters seen in the right SMA were also within the TMS and fMRI maps from our study, and consistent with previous findings that this area plays a role in motor training [Taubert et al, ].…”
Section: Discussionsupporting
confidence: 91%
“…Although these five clusters did not survive multiple comparisons correction ( P < 0.05 FWE) all changes were observed in regions that are likely to be involved with motor tasks, and all were in the right (“trained”) hemisphere. Notably, clusters at the pre‐ and postcentral gyri were consistent with the expected location of sensory and motor finger representations [Penfield and Boldrey, ; Wahnoun et al, ], and close to peaks in the (post time point) TMS and fMRI maps. All clusters were within the group‐wise region of successful TMS excitation, and all but the prefrontal cluster were consistent with regions of group‐wise fMRI activation.…”
Section: Resultssupporting
confidence: 60%
“…Using magnetoencephalography (MEG), Caetano and Jousmäki (2006) demonstrated the convergence of vibrotactile input on the superior temporal cortex of normal-hearing adults, as had been reported previously in a congenitally deaf adult ( Levänen et al, 1998 ). Recently, a vibrotactile-related endogenous neural response was mapped for purposes of surgical resection ( Wahnoun et al, 2015 ). Hegner et al (2010) found that different neuronal mechanisms underlie tactile and vibrotactile cortical processing, in which cortical representations vary depending on the nature of the stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The location of clusters in the pre-and post-central gyri were consistent with our fMRI maps, our TMS maps ( Figure 20), and with areas responsible for sensorimotor representation of the fingers elucidated through electrocorticographic and brain stimulation techniques. 233,234 The neighbouring clusters seen in the right SMA were also within the TMS and fMRI maps from our study, and consistent with previous findings that this area plays a role in motor learning. 237 That these changes appeared near the peaks of fMRI and TMS maps adds further credibility to the suggestion that changes in fMRI and TMS patterns were a reflection of altered neurite organisation, density, and/or connection strength in regions that, at baseline, were already predominantly responsible for execution of the (to-be) learned sequence, rather than altered responsibility of surrounding areas.…”
Section: Cortical Thicknesssupporting
confidence: 80%
“…Although these five clusters did not survive multiple comparisons correction (p<0.05 FWE) all changes were observed in regions that are likely to be involved with motor tasks, and all were in the right ('trained') hemisphere. Notably, clusters at the pre-and postcentral gyri were consistent with the expected location of sensory and motor finger representations, 233,234 and close to peaks in the (post time-point) TMS and fMRI maps. All clusters were within the group-wise region of successful TMS excitation, and all but the prefrontal cluster were consistent with regions of group-wise fMRI activation.…”
Section: Cortical Thicknessmentioning
confidence: 52%